Quality of Electronic Medical Record Information and Satisfaction of Electronic Medical Record Users at Pandan Arang Boyolali Regional Hospital - Sugiarsi, Sri; Mulyono, Sri; Sutrisno, Trismianto Asmo (Universitas Muhammadiyah Sidoarjo, 2024)
Information Quality can be defined as how well the function concerning the value of the output of information produced or managed by the application/ system for users can meet everyone’s expectations and will help complete their work. Information Quality measurement indicators (Riskinanto, 2016) are information quality based on accuracy value, information quality based on timeliness of delivery, and information quality based on relevance. This study aims to explaining the quality of information and user satisfaction of electronic medical records at the Pandan Arang Regional General Hospital. This study is descriptive with the aim of describing the quality of information and satisfaction of electronic medical record users. The sample was 77 people consisting of doctors, nurses and medical record officers. Primary data were collected using questionnaires. Data analysis using descriptive analysis. Results: of the information quality variable have a mean of 17.5. With a mean of 17.5, it can be concluded that the quality of information is included in the very high-quality category with an interval of 16.8-20. information satisfaction variable have a mean of 8.4. With a mean of 8.4, it can be concluded that information satisfaction falls into the satisfied category with an interval of 8.4-10. Although information satisfaction has an average value that falls into the satisfied criteria, there are still respondents who choose to be quite satisfied regarding the information satisfaction received by system users. Conclution: Electronic medical record (EMR) information quality and user satisfaction are closely related, impacting the effectiveness and adoption of EMR systems in healthcare settings. Research shows that while EMRs can improve perceived medical record quality